Coverage Evaluation of Mass Drug Administration for Lymphatic Filariasis in Mahoba District of Uttar Pradesh - Kaushal, Suneel Kumar; Maroof, Mohd; Singh, Lal Divakar; Gupta, Sandeep Kumar; Kumar, Navin (Journal of College of Medical Sciences-Nepal, 2024)
Background Lymphatic filariasis is a neglected tropical disease. In this disease patient has face hydroceale and lymphedema in leg. 863 million people had risk of lymphatic filariasis in 2020 who were belongs to 50 countries. The present study aimed to assess coverage and compliance of mass drug administration for lymphatic filariasis. Methods From 300 households (1660 individuals) in rural area was covered in coverage evaluation survey by systematic selection of subunits using PPS. Data collected by trained team and data were collected using predesigned questionnaire. MS – Excel spreadsheet used for data compilation. Results Overall, estimated 37.8% drugs were swallowed in rural area of District Mahoba. 3.7% person in study population experienced adverse drug effect. In rural area, albendazole was swallowed more by females as compared to males but reverse in case of DEC. The most common reason for both albendazole and DEC not swallowed as reported by study population was not sick. Conclusions For filariasis elimination, need to increase coverage and also increase compliance for take drug. Coverage and compliance increase by perform information education and communication activities perform with different platform.